2017
DOI: 10.3390/sports5040090
|View full text |Cite
|
Sign up to set email alerts
|

Interrepetition Rest Set Lacks the V-Shape Systolic Pressure Response Advantage during Resistance Exercise

Abstract: Resistance exercise may lead to an aneurysm due to dangerous levels of systemic hypertension. Thus, a minimized pressure response during exercise may guarantee safer training. For that, we analyzed an interrepetition rest design (IRD) hypothesizing that it would produce a lower systolic blood pressure (SBP) response in comparison with a continuous design (CD). Additionally, we studied the effect of accumulated repetitions on the increasing SBP rate during the first continuous set. Fifteen healthy participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…Specifically, there were significant time × session interactions only for RPP after the 8th and 16th repetitions. To the best of our knowledge, this is the first evidence in the literature reporting a reduced hemodynamic load during IRRT in a clinical population which agrees with previous reports with young healthy individuals [15,16]. These findings are of importance as a strategy for reducing cardiovascular risk during RT in these patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, there were significant time × session interactions only for RPP after the 8th and 16th repetitions. To the best of our knowledge, this is the first evidence in the literature reporting a reduced hemodynamic load during IRRT in a clinical population which agrees with previous reports with young healthy individuals [15,16]. These findings are of importance as a strategy for reducing cardiovascular risk during RT in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it would be expected that our SBP recordings were~31% lower in both conditions than those measured with direct methods during lifting [21]. Future studies should be conducted with continuous recording of hemodynamic responses with other measurement techniques during the whole training session to verify potential differences during peak BP responses between set configurations [16]. Second, mechanical performances and perceptual fatigue were not recorded.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although different from the dynamic exercise explored in the present study, Río-Rodríguez et al (2016) reported that intra-set rest configuration induced lower central and peripheral fatigue during an isometric knee extension exercise, reducing the cardiovascular stress. Additionally, another study comparing W:R equated RTPs (40 × 1:18.5 s vs. 5 × 8:180 s) in healthy participants found lower SBP peaks with the protocol with longer rest intervals (Mayo et al, 2017). Similarly, a previous study from our group involving normotensive participants also reported lower SBP peaks with a 9 × 5:22 s protocol in comparison with a 3 × 15:88 s protocol (Paulo et al, 2019).…”
Section: Discussionsupporting
confidence: 69%
“…These findings suggest that the intermediate protocol may be more appropriate for hypertensives than the usual one. Actually, other studies have also compared BP increase during W:R-equated RTPs (Río-Rodríguez et al, 2016;Mayo et al, 2017;Paulo et al, 2019), but none of them was conducted with hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%